Adopting statistical methods for controlling the quality of drinking water to achieve customer satisfaction - حسين احمد ابراهيم (Journal of Economics and Administrative Sciences, 2019)
The current research aims to adopt production quality decisions as the most important decisions , because they are accompanied by customer satisfaction through monitoring the quality of drinking water in iraq which reach through the pipeline network associated with water treatment projects of Tigris and Euphrates rivers. One of the indicators of quality control was the drawing of the C-chart by specifying the central line and the upper and lower limit of the control and the diagnosis of whether the production system as a whole within the scope of quality control or not and determine the strength and significance of the correlation between the quantities of water And actual needs for customers , the research has reached a number of conclusions and proposals that are appropriate to their nature .